Implementasi Pembangunan Ekonomi Berbasis Islam dalam Peberdayaan Masyarakat: Studi Kasus Republik Islam Iran - Dede Saerozi; Moh. Ridwan Maulana; Nissya Rahma Aurelia Rokhim (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2026)
The economic sanctions imposed on Iran since 2018 have not been lifted until 2024. Amidst this pressure, Iran has become a kind of open laboratory for the implementation of Islamic economics at the state level. The question is, to what extent is this system capable of empowering society when access to global finance is blocked? This study attempts to answer this by examining three pillars implemented by Iran between 2018 and 2024. First, the government issued a $2.5 billion Musharakah Sovereign Sukuk in 2023 to finance infrastructure projects without interest. Second, the Central Bank of Iran aggressively increased its gold reserves from 108 tons to 200 tons as a form of safeguard against the SWIFT blockade. Third, the distribution of zakat and waqf (waqf) began to be digitized through the Iran Electronic Zakat Fund, which by 2023 had distributed $340 million to nearly 280,000 MSMEs. This research utilizes a literature review of 42 documents, including Scopus articles from Q1–Q3, IMF and World Bank reports, and World Gold Council data. When measured against the framework of the maqasid sharia (Islamic principles), Iran appears to have successfully maintained its hifz al-din (obligatory welfare) aspect through a fully Islamic banking system. However, its hifz al-mal (obligatory welfare) aspect has faltered. As of March 2024, inflation was recorded at 45.8%, and the poverty rate reached 31.7%. The conclusion is that normative adherence to sharia principles does not automatically guarantee prosperity when geopolitical factors come into play. The synergy between sukuk, gold, and digital philanthropy does form an attractive Resistance Economy model. However, without global political stability, this model functions more as a shield than as a growth engine. These findings are important for other Muslim countries considering a similar path.